Do Environmental, Social and Governance (ESG) Performance Scores Reduce the Cost of Debt? Evidence from Indian firms - Ankit Arora; Dipasha Sharma (Australasian Accounting, Business and Finance Journal, 2022)
This study aims to assess the impact of Environmental, Social, and Governance (ESG) ratings on the cost of debt of Indian firms from the year 2015 to 2020. One of the challenges that corporate India is going to face moving forward is that regulations with respect to environmental conservation, transparency, corporate social responsibility, and corporate governance will get stricter. This will undoubtedly push the companies to follow better ethical practices, adopt fair employee policies, and safeguard the environmental policies. So, this paper intends to evaluate the ESG lens of Indian companies concerning their financing decisions, viz the cost of debt. The firms under investigation are listed on the NIFTY 500, which reflects the top 500 companies in the eligible universe based on complete market capitalization. Data was sourced from the Bloomberg database. The paper uses cost of debt as the dependent variable; ESG score & individual E, S, G scores as independent variables; Market capitalization, net debt to equity ratio, and percentage of women on board and total debt to total asset ratio as control variables. Since the data was in a panel data format, we performed panel data regression from FY2015 to FY2020, and the method used was Least Squares Method (L.S. and A.R.). Different models were considered and it was found that the cost of debt which is the dependent variable, had a negative coefficient i.e., higher the ESG score, lower the cost of debt component for the firm and according to our model, it could be significantly proven at 10% level.
Keywords: Corporate Social Responsibility (CSR); Market Capitalization; Environmental; Social and Governance (ESG); Disclosure Scores; Corporate Bonds; Stakeholders’ Theory; Fixed Income; Cost of Debt